AB0401 Anxiety and Depression in Patients with Rheumatoid Arthritis Treated with Biological Drugs: Prevalence and Relationship with Disease Activity. (9th June 2015) - Grosso, V.; De Nard, F.; Breda, S.; Monti, S.; Todoerti, M.; Caporali, R.; Montecucco, C.
Abstract : Background: Many patients with rheumatoid arthritis (RA) experience anxiety and depression, with higher presence of these disorders in those with poorer outcome [1]. Previous experiences found relationships with psychological status and disease activity in patients with active disease [2, 3]. Further evidences are needed to asses the impact on residual RA activity during treatment. Objectives: To register the prevalence of anxious (ANX) and depressive (DEP) disorders in RA patients treated with bDMARDs with stable disease and therapy and to evaluate their connection with disease activity. Methods: We assessed the presence of ANX and DEP disorders with the HADS questionnaire [4] in patients with RA treated according the EULAR 2013 recommendations with bDMARDs [5]. We registered disease activity using DAS28 score during the same day of questionnaire compiling. Patients with major changes in their DMARD therapy during the previous six months, with known diagnosis of anxiety-depressive syndrome, fibromyalgia, or treated with antidepressant drugs were excluded. The variables of interest were compared between groups with Kruskall-Wallis test. Results: We assessed 200 patients, female 171 (85%), with an overall median (IQR) age and disease duration of 62, 35 (54, 09 – 76, 03) years and 11, 24 (7, 29 – 19, 46) years respectively. At least one ANX or DEP disorder was present in 93 (46.5%) patients. In patients with ANX, DEP and with ANX*DEP disorders values of pain VAS, DAS28, GH, PGA, number of painful joints on 28 (TND28), HAQ were higher than those in HEALTY group (p<0, 01). Prednisone dosage was higher among patients with ANX or DEP disorders. Number of swollen joints on 28 (SWJ28) CRP and ESR were not different among groups. There was a moderate correlation between HADS scores and DAS28, pain VAS, PGA, GH and TND28. Conclusions: There is a high prevalence of ANX and DEP disorders in patients with RA. Patients with those disorders have higher level of residual disease based on higher subjective variables, while objective variables (SWJ28 and laboratory indexes) remain unmodified. The higher steroid doses in patients with ANX or DEP are probably due to higher disease activity measured with DAS28. References: Matcham F et al, Rheumatology (Oxford) 2013. Traki L et al, Clin Rheumatol 2014. Cordingley L et al, Arthritis Care Res (Hoboken) 2014. Zigmond AS et al, Acta Psychiatr Scand 1983. Smolen JS et al, Annals Rheum Dis 2014. Disclosure of Interest: None declared